Smart Cities in Future Energy System Architecture - Mekhdiev, Elnur T.; Prokhorova, Victoria V.; Makar, Svetlana V; Salikhov, Gafu G.; Bondarenko, Alexandr V. (International Journal of Energy Economics and Policy, 2018)
The article analyzes new technologies, which establish modern trends for future electric power systems operation and development, and their impact on production, storage, transmission, distribution and consumption of electricity. The article also studies trends and approaches to urban planning with an emphasis on energy infrastructure, where success in “smart city” and “smart grid” concepts implementation is considered as overarching question. The general requirements for smart power supply system are defined, problems that need to be solved are formulated, and a number of general recommendations are given for future development. Keywords: energy system, smart grid, smart cities JEL Classifications: L94; Q42; Q48; H54